Attention's grasp: early and late hand proximity effects on visual evoked potentials - Reed, Catherine L.; Leland, David S.; Brekke, Benjamin; Hartley, Alan A. (Frontiers in Psychology, 2013)
Behavioral studies suggest that visual attention is biased toward stimuli in the region of space near the palm of the hand, but it is unclear whether this effect is universal or selective for goal/task-related stimuli. We examined event-related potentials (ERPs) using a visual detection task in which the hand was placed near or kept far from target and non-target stimuli that were matched for frequency and visual features to avoid confounding factors. Focusing on attention-sensitive ERP components, we found that P3 (350-450 msec) amplitudes were increased for Hand Near conditions for targets only, demonstrating a selective effect consistent with the P3’s cross-modal and task-relevance influences. An N1 variant implicated in visuotactile integration (central Nd1; 120-190 msec) showed similar target-specific effects. P1 (80-110 msec) effects for target stimuli were also apparent, but may have applied to non-targets as well, which would be consistent with the P1’s association with early, pre-categorical increases in sensory gain. Collectively, these findings suggest that by the time stimuli are categorized as relevant/irrelevant for action, the proprioceptive effects of the hand on visual attention are selective for goal/task-related stimuli. At the same time, hand proximity appears to bias attention early, starting with a facilitation of processing for perhaps any visual stimuli near the hand, and continuing with enhancements that are selective to those stimuli categorized as task-relevant.